Restoration of colour channel misalignments in colonoscopy videos - Lacey, Gerard; Dahoyt, Rozenn (Trinity College Dublin, 2007)
We propose a method to restore colonoscopy videos that have low quality RGB images. The main problem concerns a time delay occurring in between the recordings of the R, G and B colour channels. As the camera is moving along in the colon, sometimes quickly, the resulting images show non properly matched R, G and B causing blurry effects that impede the medical doctors or computer-aided analysis methods. We proposed to restore this artefact by first equalizing the colour channels and then performing a robust camera motion estimation and compensation. Experimental results show significant improvements from the original videos.
Keywords: Colonoscopy; RGB images; Colour channels; Creative Technologies; Computer Vision and Image Processing